New construction materials synthesized from water treatment sludge and fired clay brick wastes - Erdoğmuş, Ertuğrul; Harja, Maria; Gençel, Osman; Sutcu, Mucahit; Yaraş, Ali; Gençel, Osman; Erdoğmuş, Ertuğrul; Yaraş, Ali (Elsevier, 2021)
Novel bricks have been produced by firing mixes of water treatment sludge (WTS) and fired clay brick waste (BW). The capitalization of sludge in the construction industry is the most economically sound option. In this study, a series of different proportioning ratios of water treatment sludge and fired clay brick waste were studied. The WTS rations were 25, 40, 55, 70, 85, and 100% of the total weight of the mixture. Each series involved the firing of bricks at 1000 degrees C for 2 h. The obtained bricks were characterized by bulk density, apparent porosity, water absorption, loss on ignition, compressive strength, thermal conductivity, efflorescence, and freeze thaw, in addition to chemical, mineralogical, and microstructural investigations. From experimental results, it was observed that obtained bricks having over 75, respectively 60% BW, had lower compressive strength compared to bricks obtained only from WTS. The loss of ignition, porosity, and water absorption values slightly decrease, while compressive strength and thermal conductivity values increase, which depends on the amount of WTS waste content. The bricks containing 70-85% WTS give better results, while the bricks containing up to 40% WTS waste present a compressive strength that is greater than twice the minimum limit. The efflorescence of all bricks is in the slight level. Tests have shown that bricks with 70-85% WTS have proper characteristics and can be effectively used as building materials. The present study demonstrated that by replacing clay (traditional bricks) with proposed wastes, eco-friendly bricks can be obtained that save resources.
Keywords: Brick Wastes; Building Materials; Recycling; Water Treatment Sludge